2015
DOI: 10.1080/13607863.2015.1043619
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect predicts everyday problem-solving ability in older adults

Abstract: Current results extend previous findings by showing that the relationship between increased depressive symptoms and decreased EPS ability in older age may be primarily driven by anhedonia as opposed to other depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Cross-sectional studies suggest that positive affect was a more robust predictor of cognitive performance across a variety of tasks than depressed affect, somatic symptoms or interpersonal difficulties (La Rue et al 1995), that higher positive affect was related to better every day problem solving (Paterson et al 2016), and that higher positive affect was related to better verbal fluency performance (before Bonferroni adjustment), but not better memory, speed or attention (Baune et al 2007). Longitudinal findings by Turner et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies suggest that positive affect was a more robust predictor of cognitive performance across a variety of tasks than depressed affect, somatic symptoms or interpersonal difficulties (La Rue et al 1995), that higher positive affect was related to better every day problem solving (Paterson et al 2016), and that higher positive affect was related to better verbal fluency performance (before Bonferroni adjustment), but not better memory, speed or attention (Baune et al 2007). Longitudinal findings by Turner et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies conducted in non-clinical populations using the Center for Epidemiologic Studies Depression Scale (CES-D) ( Radloff, 1977 ) suggest that: lower levels of depressed affect and somatic symptoms were related to better performance on tasks assessing speed, attention and executive function, whereas higher levels of positive affect were related to poorer verbal fluency performance ( Baune et al, 2007 ); higher levels of positive affect (but not lower levels of depressed affect, somatic symptoms or interpersonal difficulties) were related to better everyday problem solving ( Paterson et al, 2015 ); positive affect was the most robust predictor of cognitive performance across a variety of tasks assessing memory, processing speed, verbal fluency, visual retention, temporal orientation, and global cognition ( La Rue et al, 1995 ). Studies using the Euro-D depression scale ( Prince et al, 1999 ) found that verbal fluency performance was more strongly associated with motivational symptoms of depression than with affective suffering symptoms (Brailean et al; Castro-Costa et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be the result of good social relationships. However, positive emotions seem to affect also the problem solving process thanks to increased creativity and better cognitive capabilities (Isen et al 1987;Isen 2001;Rego et al 2014;Paterson et al 2016;Yuan 2015). In turns, this can influence also the bargaining process and the resolution of conflicts (Forgas 1994;Baron et al 1990;Kanske and Kotz 2011;Morris and Keltner 2000).…”
Section: Employmentmentioning
confidence: 99%